Island Tourism: Sustainable Perspectives - Carlsen, Jack (CABI, 2014)
There is already a signiﬁ cant body of knowledge of sustainable island tourism development presented in previous books by authors including Apostolopoulos and Gayle, 2002 (Island Tourism and Sustainable Development: Caribbean, Paciﬁ c and Mediterranean Experiences), Briguglio et al., 1996 (Sustainable Tourism in Islands and Small States: Issues and Policies) and Briguglio et al., 1996 (Sustainable Tourism in Islands and Small States: Case Studies), among others. These previous volumes, along with this present book, would not have materialized without the contributions of the numerous island tourism researchers dedicated to developing an understanding of the important and complex topic of sustainable island tourism development. The chapters in this book are all based on original research and were subject to peer review before publication. This growing interest in studying island tourism development from a sustainable perspective is probably attributable to the fact that islands form perfect ‘living laboratories’ that enable researchers to isolate the causal and immediate effects of tourism development on the community, environment and economy of islands, and to study them at a level of detail that is not possible in other tourism destinations. Islands attract not only tourists, but also those who seek to study the effects of tourism, and the chapters in this book add to that substantial body of research from the perspective of sustainable tourism researchers. Additionally, research questions and implications arising from each of the chapters are included in the ﬁ nal chapter, which will stimulate interest in speciﬁ c topical or geographical areas of future research.